STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU PADA SMP NEGERI 16 KOTA BANDA ACEH - Maiyuli .; Yusrizal .; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
Increased teacher competence is influenced by the strategy and role of the principal. The purpose of this study to know and analyze the program, strategy, evaluation and also, the supporting factors and obstacles of the Principal in improving teacher competence. Descriptive qualitative research methods, observation data collection techniques, interviews, and documentation studies, the subject is the principal, vice principal, teachers and administrative selected purposively. The results of the study show that: 1) The principal's program in improving teacher competence is done by requiring certified students to purchase books, and with MGMP school and MGMP integrated training / training activities 2). Principal strategies in improving teacher competence by analyzing initial needs, from the results of the new analysis determined what should be done to improve teacher competence, encourage teachers to pursue higher education and introduce school culture by creating a conducive school. 3) Principal evaluation of teacher competency improvement through direct supervision into the classroom, and supervision by school superintendents. 4) Principal supporting factors in improving the competence of teachers is very good, and parents' contributions are very supportive because some parents are instructors at national and regional levels, supported again by teachers at SMP Negeri 16 is a national and regional level instructors. Constraints faced by the principal in improving teacher competence, limited time available, and limited budget.Keywords: teacher strategy, competency, principal, teacher’s competency